2012
DOI: 10.1186/ar3813
|View full text |Cite
|
Sign up to set email alerts
|

Smoking interacts with HLA-DRB1 shared epitope in the development of anti-citrullinated protein antibody-positive rheumatoid arthritis: results from the Malaysian Epidemiological Investigation of Rheumatoid Arthritis (MyEIRA)

Abstract: IntroductionRheumatoid arthritis (RA) is a multifactorial autoimmune disease in which genetic and environmental factors interact in the etiology. In this study, we investigated whether smoking and HLA-DRB1 shared-epitope (SE) alleles interact differently in the development of the two major subgroups of rheumatoid arthritis (RA), anti-citrullinated proteins antibody (ACPA)-positive and ACPA-negative disease, in a multiethnic population of Asian descent.MethodsA case-control study comprising early diagnosed RA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 22 publications
(46 reference statements)
4
61
0
Order By: Relevance
“…Studies initially performed by Klareskog and colleagues demonstrated a strongly significant multiplicative GEI between cigarette smoking and HLA-DRB1 in determining RA risk. 42, 72–76 This association was strongest for seropositive RA and has been replicated in several populations, including US women, and Swedish, and Malaysian populations. 72–74 The presence of heavy smoking and two HLA-DRB1 genes increased the odds for RA by 23-fold compared to those with neither risk factor.…”
Section: Introductionmentioning
confidence: 75%
“…Studies initially performed by Klareskog and colleagues demonstrated a strongly significant multiplicative GEI between cigarette smoking and HLA-DRB1 in determining RA risk. 42, 72–76 This association was strongest for seropositive RA and has been replicated in several populations, including US women, and Swedish, and Malaysian populations. 72–74 The presence of heavy smoking and two HLA-DRB1 genes increased the odds for RA by 23-fold compared to those with neither risk factor.…”
Section: Introductionmentioning
confidence: 75%
“…In other instances (such as reactive arthritis), the genetic component can be much less prominent, with the microbial component being the dominating trigger. In RA, established risk factors, including smoking status and sex, influence the gut microbiota, with the effect of smoking on ACPA production being particularly obvious in patients carrying HLA-DRB1 shared-epitope alleles 137,[151][152][153][154][155] . The principal difference between the multidirectional and the linear models is the reversibility of the multidirectional model.…”
Section: Other Rheumatic Diseasesmentioning
confidence: 99%
“…Xue et al 20 found that the SE was associated with RA but not with ACPA production in a small Chinese RA cohort, whereas such associations have been reported in Malaysian, Chinese and Japanese patients 21 22. In a mixed Malaysian population, smoking, the SE and the interaction between them, only conferred risk for ACPA-positive RA 23. However, in a Korean population, Bang et al 16 reported that the SE was associated with ACPA-negative and ACPA-positive RA.…”
Section: Introductionmentioning
confidence: 97%